Review of the genera Hishimonus Ishihara and Litura Knight(Hemiptera: Cicadellidae) from the Indian subcontinent with description of new species - Viraktamath, C. A.; Murthy, H. V. Anantha (Zootaxa, 2014)
This paper deals with 21 species of Hishimonus Ishihara and two species of Litura Knight from the Indian subcontinent. The following new species are described: Hishimonus acuminatus sp. nov. (India: Mizoram), H. distinctus sp. nov. (India: Karnataka, Kerala, Tamil Nadu. Sri Lanka), H. dwipae sp. nov. (Sri Lanka), H. longisetosus sp. nov. (India: Karnataka), H. spicans sp. nov. (India: Karnataka), H. thapai sp. nov. (Nepal), H. zeylanicus sp. nov. (Sri Lanka), and Litura triangula sp. nov. (India: Karnataka). Hishimonus versicolor Subba Rao & Ramakrishnan is removed from the genus Hishimonus and two new combinations namely, Hishimonus apricus (Melichar) comb. nov. (formerly in the genus Eutettix) and Litura tripunctatus (Li) comb. nov. (formerly in the genus Hishimonus) and a new name Hishimonus knightiella nom. nov. for Hishimonus apricus Knight 1970a, not Distant 1908 is proposed. H. gillespiei Dai, Fletcher & Zhang, H. pallidus Dai, Fletcher & Zhang, H. dividens Knight, H. aberrans Knight, H. concavus Knight, H. arcuatus Knight and Litura unda Knight are new records for India. All the taxa are described and new taxa are illustrated. Keys to identification of the species of Hishimonus and Litura found in the Indian subcontinent are also provided along with list of known host plants.